PREIMPLANTATION GENETIC TESTING FOR ANEUPLOIDY (PGT-A) AND NON-INVASIVE PRENATAL TESTING (NIPT) AS KEY COMPONENTS OF CONTEMPORARY PREGNANCY MANAGEMENT (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The rapid development of reproductive genetics has substantially influenced current approaches to pregnancy planning and prenatal care. Preimplantation genetic testing for aneuploidy (PGT-A) and non-invasive prenatal testing (NIPT) are innovative screening methods designed to identify chromosomal abnormalities at different stages of human development. PGT-A is performed prior to embryo implantation during assisted reproductive technology cycles, while NIPT allows early assessment of fetal chromosomal status through maternal blood analysis. The combined use of these methods contributes to improved reproductive outcomes, reduction of pregnancy loss, and optimization of individualized pregnancy management. This article provides an analytical overview of the principles, clinical significance, advantages, limitations, and ethical aspects of PGT-A and NIPT in modern obstetric practice.
Keywords: In vitro fertilization, pregnancy management, diagnostic challenges, reproductive outcomes.